Comparative study of substance P and neurokinin A in gingival crevicular fluid of healthy and painful carious permanent teeth - Alireza Heidari; Mahdi Shahrabi; Mehrak Rokouei; Aliakbar Amirzargar; Pegah Rahbar (Wolters Kluwer Medknow Publications, 2017)
Background: It is shown that neuropeptides can be transported from pulp chamber to periodontal ligament through apical foramen and accessory canals. Therefore, clinical pulpal pain leads to expression of preinflammatory neuropeptides such as substance P (SP) and neurokinin A (NKA) in gingival crevicular fluid (GCF). This study aimed to evaluate levels of SP and NKA in GCF of carious and healthy permanent teeth, comparatively. Materials and Methods: This cross-sectional study was performed on twenty children referred to Department of Pediatric Dentistry, Tehran University of Medical Sciences, who had a painful permanent first molar. Sampling was done by sterile paper cone from GCF of the mentioned teeth and the intact tooth of the other side of the jaw in the same patient. Values of SP and NKA were measured by ELISA test. Results: The mean concentration of SP in GCF of painful carious and healthy teeth was 2.65 ± 0.56 and 1.83 ± 0.65 pcgr/ml, respectively. This value was 2.29 ± 0.29 and 1.61 ± 0.35 pcgr/ml for NKA concentration in carious and healthy teeth as well. Conclusion: Significant higher levels of both SP and NKA in GCF of painful carious teeth were observed, which is in line with previous studies' findings.